Sosialisasi Proses Pembuatan Tahu yang Sehat untuk Masyarakat di Pasar 4 Medan Marelan - Afdillah; Hasibuan, Selly Oktadiah; Fitrah, Harisa; Ritongga, Jenaf; Simbolon, Nur Amalia; Daulay, Rabiyah Afifah (At-Tadris: Journal of Islamic Education, 2023)
Tofu has the highest quality vegetable protein because it contains the most amino acids and is thought to be easy to digest (85%-98%). This tofu product has been available since 2018 from its Medan address, specifically at jl. Hanif Hj. The purpose of this study was to ascertain how small-scale industrial production of tofu has developed on Jl. In this study, Hj Hanif employs a descriptive qualitative method to describe and analyze the findings in light of the conditions or conditions that are encountered in the field. The methods used to collect data include: Others: 1) Informant observation, 2) Interviews, and 3) Documentation The use of quality, the availability of fuel, and the technology for steam boilers all contributed to the development of a small industry. The purpose of this research is to ascertain the tofu processing procedure. The primary raw materials for the tofu processing process in the tofu industry are soybean seeds, which are processed through soaking, washing, cooking, filtering, settling, adding vinegar, printing, pressing, and cutting. The ingredients used in the production process are vinegar, acetic acid, and water.